AUTOMORPHISMS OF DISTANCE-REGULAR GRAPH WITH INTERSECTION ARRAY {39; 36; 4; 1; 1; 36} - Konstantin S. Efimov; Aleksandr A. Makhnev (Ural Mathematical Journal, 2018)
Makhnev and Nirova have found intersection arrays of distance-regular graphs with no more than \(4096\) vertices, in which \(λ=2\) and \(μ=1\). They proposed the program of investigation of distance-regular graphs with \(λ=2\) and \(μ=1\). In this paper the automorphisms of a distance-regular graph with intersection array \(\{39,36,4;1,1,36\}\) are studied.